Reproducibility and long-term stability of Sn doped MnO2 nanostructures: Practical photocatalytic systems and wastewater treatment applications. (April 2022) - Panimalar, S.; Subash, M.; Chandrasekar, M.; Uthrakumar, R.; Inmozhi, C.; Al-Onazi, Wedad A.; Al-Mohaimeed, Amal M.; Chen, Tse-Wei; Kennedy, J.; Maaza, M.; Kaviyarasu, K.
Abstract: Sn-doped MnO2 were synthesized as an oxidant, a mediator of maleic acid (C4 H4 O4 ) and SnCl2 as doping ingredient via a basic sol-gel reaction with KMnO4 . XRD study signposts that tetragonal crystal structure of MnO2 (ICDD#44-0141) with a plane group of 12/m (87) for both pure and Sn doped MnO2 nanostructures. The photocatalyst synthesized has mesoporosity, allowing to the N2 adsorption/desorption experiments. The geometry of the materials varies from spherical shape in pristine MnO2 to a rod-like shape in Sn-MnO2, as observed in the SEM and TEM pictures. To examine optic properties and energy bandgaps topologies, UV–visible diffuse reflectance spectroscopy was applied. In visible spectrum, overall catalytic performance of Sn-doped MnO2 was tested using methyl orange and phenol as dyes. The results suggest that the optimized Sn doped MnO2 (10 wt.%) catalyst showed higher degradation efficiency (98.5%), apparent constant (0.7841 min −1 ) and long term permanence. For this improved charge extraction efficiency, a potential photocatalytic mechanism was proposed. Graphical abstract: Image 1 Highlights: Structural and optical properties of tin doped MnO2 nanoparticles were studied. α-MnO2 crystalline planes and coincide well with reference peaks of tetragonal MnO2 . MnO2 has spherical-like particles with a diameter of approximately 30 nm. the measured PL spectra showed 3 distinct emission peaks at 411 nm, 460 nm & 491 nm. Sn doped MnO2 photocatalyst show high degradation of MO (79.2%) & phenol (98.5%).